Myocardial Scar Delineation Using Diffusion Tensor Magnetic Resonance Tractography. Issue 3 (2nd February 2018) - Mekkaoui, Choukri; Jackowski, Marcel P.; Kostis, William J.; Stoeck, Christian T.; Thiagalingam, Aravinda; Reese, Timothy G.; Reddy, Vivek Y.; Ruskin, Jeremy N.; Kozerke, Sebastian; Sosnovik, David E.
Abstract : Background: Late gadolinium enhancement (LGE) is the current standard for myocardial scar delineation. In this study, we introduce the tractographic propagation angle (PA), a metric of myofiber curvature (degrees/unit distance) derived from diffusion tensor imaging (DTI), and compare its use to LGE and invasive scar assessment by endocardial voltage mapping. Methods and Results: DTI was performed on 7 healthy human volunteers, 5 patients with myocardial infarction, 6 normal mice, and 7 mice with myocardial infarction. LGE to delineate the infarct and border zones was performed with a 2‐dimensional inversion recovery gradient‐echo sequence. Ex vivo DTI was performed on 5 normal human and 5 normal sheep hearts. Endocardial electroanatomic mapping and subsequent ex vivo DTI was performed on 5 infarcted sheep hearts. PA in the normal human hearts varied smoothly and was generally <4. The mean PA in the infarct zone was significantly elevated (10.34±1.02 versus 4.05±0.45, P <0.05). Regions with a PA ≤4 consistently had a bipolar voltage ≥1.5 mV, whereas those with PA values between 4 and 10 had voltages between 0.5 and 1.5 mV. A PA threshold >4 was the most accurate DTI‐derived measure of infarct size and demonstrated the greatest correlation with LGE ( r =0.95). Conclusions: We found a strong correlation between infarct size by PA and LGE in both mice and humans. There was also an inverse relationship between PA values and endocardial voltage. The use of PA may enable myocardial scar delineation and characterization of arrhythmogenic substrate without the need for exogenous contrast agents.